The linkage between phytoplankton productivity and photosynthetic electron transport in the summer from the Changjiang River to the East China Sea - Fei, Shuyi; Gao, Yonghui; Li, Ji; Cao, Lingzhi (Frontiers in Marine Science, 2024)
Variable fluorescence measurements provide automatic and rapid estimates of electronbased photosynthesis. However, electron transport rates (ETR) to phytoplankton production varied greatly due to biological physiology and environmental stress along the Changjiang River to the adjacent seawater, where the turbid riverside, nutrient-rich river plume, and seawater can be divided with the sediment front and plume front. We assessed the light responses of ETR, 18 O-labeled gross primary production (GPP), and O2-based net community production (NCP) in the bloom season at the Changjiang River Estuary. The phytoplankton distribution and potential photosynthesis efficiency were positively related, exhibiting the offshore decreasing trends and the peak surrounding the upwelling. The conversion factor of Φ GPP (mol e -per mol O2 production) ranged from 0.8 to 31.8 and Φ NCP from 0.9 to 36.9, respectively. Φe: O increased from the nutrient-rich Changjiang diluted water (CDW) to the nutrient-poor seawater. Although Φ GPP and Φ NCP were linearly related to non-photochemical quenching (R 2 > 0.5) in the CDW, this relationship decoupled in offshore seawater that is constrained by P-limitation, light stress and the shift of the phytoplankton community. A better relationship of Φ GPP and Φ NCP was quantified with light attenuation coefficient (Kd), euphotic depth (Zeu), salinity, nutrient, and temperature (p < 0.001) using multiple linear analyses. This improvement in accuracy provides a major step forward for widespread and accurate fluorometry-based GPP and NCP application at high temporal and spatial resolution in the future.